Belize report for the Fourth World Conference on Women (Beijing 1995) : action for equality, development & peace - Johnson,Robert (Ministry of Human Resources, Youth, Women & Culture BelmopanBZ, 1994)
Provides a general profile of Belize. Reviews and appraises the status of women at the national level. Reviews and appraises international support and looks at future strategic and finiancial arrangements.